Oxford case histories in sleep medicine - Makker, Himender; Walker, M. C. (Matthew Charles); Selsick, Hugh; Kotecha, Bhik; Johal, Ama ([Oxford] : Oxford University Press, 2015)
This title provides a case-based approach to the understanding of common and important sleep disorders as well as primary neurological sleep disorders. The case histories are written by experts from University College London Hospitals with long-standing experience of providing a multi-disciplinary approach to the management of sleep disorders.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 15, 2016).
Keywords: Sleep disorders